The Learning Model of Project-Based Learning (PjBL) on the Resilience of Students' Misfortunes - Sayang Pradnyani, I Dewa Ayu; I Made Citra Wibawa (MIMBAR PGSD Undiksha, 2023)
The low resilience of students can be seen from their inability to face challenges and difficulties in the learning process. The lack of application of learning models that involve problem-solving results in students complaining when faced with difficult material and questions. As well as students refuse when given project-based assignments. This study aimed to examine the effect of the Project Based Learning (PjBL) learning model on students' resilience. The research method is quantitative with Quasi-Experimental Design by applying the PjBL learning model to the Experiment class and not applying the PjBL model to the control class. The study population consisted of 160 people, with a sample of 34 people for the experimental class and 36 for the control class. Collecting data with a non-test is a questionnaire, and the instrument is a questionnaire. The data analysis techniques are descriptive and inferential statistics (t-test). The results of testing the hypothesis showed a significant effect of the PjBL model on students' resilience. It was concluded that the PjBL model could improve the resilience of students.